Cognitive Profile of Patients With Mitochondrial Chronic Progressive External Ophthalmoplegia - Zhang, Guanyu; Hou, Yue; Wang, Zhaoxia; Ye, Zheng (Frontiers in Neurology, 2020)
Mitochondrial chronic progressive external ophthalmoplegia (CPEO) is a major manifestation of human mitochondrial encephalomyopathies. Previous studies have shown cognitive deficits in patients with mitochondrial diseases. However, these studies often included patients with heterogeneous subtypes of mitochondrial diseases. Here, we aimed to provide a better cognitive profile of patients with CPEO by applying a comprehensive battery of neuropsychological assessments in a pure sample of patients with CPEO. We recruited 28 patients with CPEO (19 women, age 16–62 years) and 38 age- and education-matched healthy control subjects (25 women, age 16–60 years). The neuropsychological assessments covered global cognition and five cognitive domains (executive functions, language, working memory, memory, and visuospatial functions). We found that the patients were impaired in global cognition [Montreal Cognitive Assessment (MoCA)], executive functions [Trail Making Test Part B (TMT-B)], and language [Boston Naming Test (BNT)], but not in working memory, memory or visuospatial functions. Moreover, individual patients' performances in the TMT-B (completion time) were predicted by the severity of non-ophthalmoplegia mitochondrial symptoms/signs [Newcastle Mitochondrial Disease Adult Scale (NMDAS)] and duration of the mitochondrial disease (years). Namely, patients with more severe non-ophthalmoplegia mitochondrial symptoms/signs and a longer disease duration took a longer time to complete the TMT-B. No clinical measures predicted individual patients' performances in the BNT.